Fluid Inclusion Evidence for Oil Charge and Cracking in the Cambrian Longwangmiao Dolomite Reservoirs of the Central Sichuan Basin, China - Xuewei Xiao; Honghan Chen; Chunquan Li; Xiuyan Liu; Zecheng Wang; Hua Jiang (Geofluids)
The Cambrian Longwangmiao gas reservoirs in the Moxi area of the Sichuan Basin have a complex associated gas accumulation history. Based on core and thin section examination, fluid inclusion analyses and 1-D burial-thermal modelling, the diagenetic evolution and hydrocarbon accumulation processes in the Longwangmiao Formation have been reconstructed. Various diagenetic events were identified, making up a complete pore fill sequence as follows: solid bitumen/dolomite→ nonfluorescent solid bitumen → dolomite → quartz/yellow fluorescent oily bitumen → residual hole. Analyses of oil inclusions and bitumen-bearing inclusions are key to the understanding of the hydrocarbon accumulation processes. The Th values of the aqueous inclusions that are contemporaneous with hydrocarbon inclusions range from 74.3 to 214.3°C. In conjunction with burial-thermal history modelling results, the results indicate that there were two stages of oil charge and three stages of natural gas accumulation in the Longwangmiao carbonate reservoirs. The two stages of oil charge occurred in the Late Silurian and Middle Triassic, respectively. Three gas accumulation events occurred in the Middle to Late Triassic, Middle Jurassic to Early Cretaceous, and Late Cretaceous, respectively.